Qualitative study to explore the health and well-being impacts on adults providing informal support to female domestic violence survivors. Issue 3 (24th March 2017) - Gregory, Alison; Feder, Gene; Taket, Ann; Williamson, Emma
Abstract : Objectives: Domestic violence (DV) is hazardous to survivors' health, from injuries sustained and from resultant chronic physical and mental health problems. Support from friends and relatives is significant in the lives of DV survivors; research shows associations between positive support and the health, well-being and safety of survivors. Little is known about how people close to survivors are impacted. The aim of this study was exploratory, with the following research question: what are the health and well-being impacts on adults who provide informal support to female DV survivors? Design: A qualitative study using semistructured interviews conducted face to face, by telephone or using Skype. A thematic analysis of the narratives was carried out. Setting: Community-based, across the UK. Participants: People were eligible to take part if they had had a close relationship (either as friend, colleague or family member) with a woman who had experienced DV, and were aged 16 or over during the time they knew the survivor. Participants were recruited via posters in community venues, social media and radio advertisement. 23 participants were recruited and interviewed; the majority were women, most were white and ages ranged from mid-20s to 80. Results: Generated themes included: negative impacts on psychological and emotional well-being of informal supporters, and related physical health impacts. Some psychological impacts were over a limited period; others were chronic and had the potential to be severe and enduring. The impacts described suggested that those providing informal support to survivors may be experiencing secondary traumatic stress as they journey alongside the survivor. Conclusions: Friends and relatives of DV survivors experience substantial impact on their own health and well-being. There are no direct services to support this group. These findings have practical and policy implications, so that the needs of informal supporters are legitimised and met.